2006
DOI: 10.1002/masy.200651346
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Foster Swelling Degree in Polystyrene/Clay Nanocomposites Obtained by In Situ Incorporation

Abstract: During the in‐situ incorporation of an organophilic clay into the polymer matrix in a free radical polymerization, the radical should penetrate the basal space between the layers of the clay increasing the distance between these layers and leading to a nanocomposite with an intercalated or exfoliated morphology. The final morphology depends on the affinity of the monomer for the cation used to change the organophilicity of the clay. In this work, Foster swelling is applied as a method to obtain a degree of aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 8 publications
1
5
0
1
Order By: Relevance
“…Fu and Qutubuddin [1] determined the swelling behavior of organoclays in styrene comparing wettability and rheology measurements and observed that the organoclay prepared with a styryl group had the highest compatibility with styrene and formed exfoliated polystyrene nanocomposites while the organoclays that presented weaker interaction formed intercalated polystyrene nanocomposites after polymerization of styrene and organoclay mixtures. Similar results were observed by Arioli et al [3] when comparing the swelling volume of organoclays in styrene. The higher the swelling volume the higher the degree of organoclay exfoliation in polymer matrix after polymerization of styrene in the presence of organoclay.…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…Fu and Qutubuddin [1] determined the swelling behavior of organoclays in styrene comparing wettability and rheology measurements and observed that the organoclay prepared with a styryl group had the highest compatibility with styrene and formed exfoliated polystyrene nanocomposites while the organoclays that presented weaker interaction formed intercalated polystyrene nanocomposites after polymerization of styrene and organoclay mixtures. Similar results were observed by Arioli et al [3] when comparing the swelling volume of organoclays in styrene. The higher the swelling volume the higher the degree of organoclay exfoliation in polymer matrix after polymerization of styrene in the presence of organoclay.…”
Section: Introductionsupporting
confidence: 89%
“…In situ incorporation is an effective route to obtain polystyrene/clay nanocomposites [1][2][3][4][5][6][7][8][9][10]. Nonetheless, the compatibility between monomer and organoclay is a critical factor in determining the microstructure of nanocomposites obtained through in situ incorporation [1].…”
Section: Introductionmentioning
confidence: 99%
“…To understand the behavior of modified montmorillonite in the styrene monomer solution, and relate this to final nanocomposite morphologies, solution SAXS and cryogenic-TEM were performed on the styrene monomer solutions containing organo-clays after vortex mixing and sonification. It has been observed that an important indicator of the chemical compatibility between organo-clay and a solvent or monomer is the swelling behavior of the clay in the solvent or monomer, with higher swelling degrees leading to better dispersion in the final composite. , …”
Section: Resultsmentioning
confidence: 99%
“…Some researchers claimed that interaction between OMt and organic medium can be predicted by swelling degree of OMt in the organic medium [23,[28][29][30]. In order to determine the affinity level of OMt to monomers, swelling degrees of the OMts were measured in BA-MMA monomer mixture.…”
Section: Structural Characterizationmentioning
confidence: 99%